Systematic Review of Employee Performance - Iwan Setiawan; Kun Ismawati; Abdul Halik (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aims to analyze the factors that influence employee performance using a systematic observation method. A systematic review is a literature observation method that uses a systematic and transparent approach to identify, disseminate, and synthesize all research relevant to a particular research question. There are seventeen articles that are used as reference materials by the author with various variables and diverse results. The number of variables that can significantly influence employee performance indicates that employee performance is one of the important aspects in the sustainability of an organization or company in achieving goals and success both directly and indirectly. \